On Macrothrix agsensis Dumont, Silva-Briano & Babu, 2002 (Cladocera: Anomopoda: Macrothricidae), with description of the male and ephippial females, and comments on the distribution of the genus in Mexico - Garfias-Espejo, Tania; Elías-Gutiérrez, Manuel; Silva-Briano, Marcelo (Zootaxa, 2007)
The Macrothrix rosea-triserialis group of species (Cladocera: Macrothricidae) is characterized by (1) a well developed postabdomen heel; (2) rows of strong spines on preanal margin of postabdomen and (3) scraper 5 of limb II with enlarged subapical teeth. Macrothrix agsensis, a member of this group, was recently described from the Mexican Central Plateau based on parthenogenetic females only. It is characterized by five rows of long spines in the female antenna I, and five thick spines on setae 4–5 of endite 2 of limb I. Here we describe its ephippial females and males, as well as development of the latter. The ephippium is strongly chitinized, with a special ornamentation in the form of hexagonal cells. The male is characterized by peculiar groups of long and short spinules in the anterior half of the antenna I, three furrows with spinules on the male copulatory hook on limb I, and a longer seta in the outer distal lobe, armed with bean-like projections. With regard to the known distribution of Macrothrix in Mexico, it is now feasible to consider the existence of four possible endemic species in this region: Macrothrix mexicanus, M. agsensis, M. sierrafriatiensis and M. marthae. All of them, except the last one, are restricted to the Central Plateau. Another species, Macrothrix smirnovi, was described from Mexico and later found in Sacramento (USA). Among the widespread species are Macrothrix elegans and M. spinosa, the former one of the most common macrothricids in the Neotropics. It shows a northern distributional limit at the northwest of Mexico and it is possible to find it from north to south. Macrothrix hirsuticornis, restricted to North America has a southern limit in the north. Macrotrhix spinosa is found from north to south of Mexico, but its distribution range extends to South America. Other old records are doubtful, such as Macrothrix triserialis, M. rosea and M. laticornis, because they seem to be restricted to the old world.